A203 INCIDENCE AND PREDICTORS OF NON-HEPATIC CANCERS IN ALCOHOL RELATED LIVER DISEASE IN THE WALDO COHORT. (21st February 2022) - Hindi, Z; Brahmania, M; Arab, J; Shi, N; Rajoriya, N; Aithal, G; Allison, M; Hagström, H; Likhitsup, A; McCune, A; Masson, S; Parker, R
Abstract: Background: Alcohol-related liver disease (ArLD) accounts for 48% of cirrhosis-related deaths in the world. Alcohol is a known contributor to hepatocellular carcinoma (HCC) and non-hepatic cancers (NHC). Aims: We aimed to describe the incidence and predictors of NHC in patients with histologically characterized ArLD. Methods: Data came from an international, multicenter retrospective cohort study of patients with histologically characterized ArLD. We excluded all patients with clinical, biochemical, or histologic evidence of liver disease due to another etiology noted either at diagnosis or during follow-up. The primary outcome was incidence of the first of NHC. To identify risk factors of NHC, baseline characteristics of patients with and without NHC were compared. Outcomes were presented as unadjusted and adjusted hazard ratios (HR) based on COX analysis. All statistical analysis was done in R using the 'cmprsk' package. Results: A total of 633 patients with histologically characterized ArLD were included. The mean age was 51 years, 64% of patients were male and 58% had cirrhosis on biopsy. We found that 69 patients with ArLD (11%) developed NHC during a median follow-up of 8.8 years. The most common NHC was lung cancer (19%). Other cancers are shown in Figure 2. Patients who developed NHC were older (55 vs. 50 years old; p<0.0001) compared to those without NHC. BMI, current or past smoking status, peak alcohol use, absence of cirrhosis and histological findings did not differ between groups. On multivariable analysis, past smoking status (HR 5.70, p=0.002) and current smoking status (HR 4.95; p = 0.003) were associated with higher rates of NHC. Conclusions: In this large multicenter cohort study, we found ArLD is associated with an increased incidence of NHCs, primarily lung cancer. Past and current smoking are risk factors associated with an increased risk of NHC in ArLD. Funding Agencies: None